The Phylogeny of the Genera of Biting Midges (Diptera: Ceratopogonidae) of the World - Borkent, Art (Zootaxa, 2024)
A phylogenetic analysis of all extant genera of Ceratopogonidae worldwide indicates there are now 109 valid genera, including two that are unnamed. All potential morphological features were considered, with 364 adult characters surveyed. Of these 146 adult characters were considered informative and these were combined with 40 pupal features previously interpreted by Borkent (2014), 16 larval and two egg characters. The resulting phylogeny confirmed the relationships between the early lineages including Leptoconopinae, Forcipomyiinae and Culicoidini (other than Washingtonhelea) previously interpreted. The remainder are Ceratopogoninae and these are divided into 11 tribes of which four are new: Washingtonheleini, Parabezziini, Neurobezziini and Echinoheleini. The last three were previously considered as members of the Ceratopogonini. Remaining Ceratopogonini are still recognized as a paraphyletic group, with some lineages poorly resolved phylogenetically. Some genera are realigned within the tribes Sphaeromiini, Johannsenomyiini and Palpomyiini. Poorly understood genera are discussed in some detail. Available autapomorphies of genera are presented, showing that some genera lack evidence of monophyly. Previously considered features of adults as well as those newly investigated but found to be of uncertain value phylogenetically are presented and discussed in detail. Previously published phylogenetic interpretations are discussed in the light of the current analysis. Six extant genera are newly placed, three as new synonyms and three lowered in rank from full genera to subgenera (with their type species subsequently as new combinations. Another is once again placed in synonymy and one, previously considered a generic synonym is recognized as a valid genus. The changes are as follows. Guihelea Yu & Qian, in Yu et al. 2005: 1496. New synonym of Johannsenomyia Malloch 1915: 332. Johannsenomyia jingxiensis (Yu & Qian, in Yu et al. 2005): 1497. New combination. Heteroceratopogon Wirth & Grogan 1988: 55. New synonym of Ceratopalpomyia Szadziewski 1988: 171. Ceratopalpomyia poguei (Wirth & Grogan 1988: 57 (Ceratopalpomyia). New combination. Hypsimyia Yu, in Yu et al. 2005: 1433. New synonym of Ceratopogon Meigen 1803: 261. Ceratopogon emeiensis (Yu & Li, in Yu et al. 2005): 1433 (Hypsimyia). New combination. Chairopogon Yu, in Yu et al. 2005: 1430. New status as subgenus of Culicoides Latreille 1809: 251. Culicoides (Chairopogon) chengdeiensis (Yu & Hao, in Yu et al. 2005): 1430 (Chairopogon). New combination. Oxyria Yu, in Yu et al. 2005: 1436. New status as subgenus of Forcipomyia Meigen 1818: 73, 75. Forcipomyia (Oxyria) xui (Yu, in Yu et al. 2005): 1437 (Oxyria). New combination. Sinicohelea Yu, Wang & Tan, in Wang et al. 2012: 42. New status as subgenus of Forcipomyia Meigen, 1818: 73, 75. Forcipomyia (Sinicohelea) xuanjui (Yu, Wang & Chen, in Wang et al. 2012) (Sinicohelea). New combination. The type species of Paralluaudomyia is once again named Alluaudomyia maculata (Clastrier 1960) and the genus is a synonym of Alluaudomyia. New status. Boreohelea was most recently considered a synonym of Allohelea and is now returned to generic status. New status.